RANCANG BANGUN SISTEM INFORMASI SEKOLAH BERBASIS WEB MENGGUNAKAN CMS FORMULASI - Fatsyahrina Fitriastuti; Septiana Mundianarti (Informasi Interaktif, 2016)
CMS (Content Management System) in general is a system that provides convenience to users in managing and making changes to the content of a website without the technical knowledge provided. That is, everyone is free to create, delete, or even update the contents of the website without interference from the webmaster. Technically CMS separates the content and design so consistency of the display is always well preserved. Each section of the website can have different content and appearance, without having to worry about losing the identity of the website as a whole. All data is stored in one place making it easy to reuse information for various purposes. CMS also makes flexible workflow arrangements or work flow and permissions so as to increase the chance of users adapt in developing the website. There are various CMS that have been frequently used to build websites, such as WordPress, Joomla, Drupal, Moodle, Formulation and so forth. This research uses CMS Formulation to design and build school based information system website with case study at SD Negeri Jlaban Sentolo Kulon Progo. The result of this design is a website-based school information system that can facilitate the delivery of information to students, parents / guardians and the wider community such as school profiles, school news, school announcements, school activities, school activities, teacher data, student data, staff data , Alumni data and photo gallery activities.Keyword: CMS Formulasi, sistem informasi, website, SD Negeri Jlaban